Rekonstruksi Asesmen Akidah Akhlak Berbasis Kebiasaan Harian Peserta Didik Pada Madrasah Tsanawiyah - Mukhlasin; Moh Sahlan (Al-Khazin: Jurnal Pendidikan Agama Islam, 2026)
Learning Akidah Akhlak has a strategic role in shaping the character and personality of students based on Islamic values. However, the assessment practice that has been applied so far is still dominated by the measurement of cognitive aspects through written tests so that it has not been able to describe the internalization of moral values in its entirety. This article aims to examine the reconstruction of the assessment of Moral Faith based on students' daily habits as an alternative to evaluation that is more authentic and relevant to the goals of Islamic education. The research uses the library research method by analyzing various scientific sources related to authentic assessment, character education, moral creed learning, and habituation theory in Islamic education. The results of the study show that daily habit-based assessments are able to provide a more comprehensive picture of the development of students' morals through behavioral indicators that appear in daily life. This assessment model can be applied through continuous observation, teacher journals, self-assessments, peer assessments, and character portfolios. The reconstruction of the assessment is expected to be able to reduce the gap between academic achievement and the implementation of moral values in the lives of students.